Analisis Pengaruh Penghindaran Pajak dan Profitabilitas Terhadap Nilai Perusahaan Sektor Barang Konsumsi Tahun 2019-2023 - Hallatu, Cindy W. C.; Salle, Agustinus; Tandililing, Elia M.; Rofingatun, Siti; Bleskadit, Novalia H.; Kambuaya, Maylen K. P (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2025)
The purpose of this study was to analyze the influence of various factors, namely tax avoidance and profitability on firm value. The samples used in this study were 6 companies. This study uses version 29 of the SPSS software application as a research data test tool for 30 samples in this study. This study uses samoel from manufacturing companies in the consumer goods sub- sector listed on the IDX for the 2019-2023 period. The method used for retrieval is using the porpusive sampling method. This study uses the classic assumption test and hypothesis testing. The results of this study indicate that tax avoidance has a positive effect on firm value, while profitability has a negative effect on firm value.Keywords: tax avoidance, profitability, firm value